ATTITUDES OF HEALTH WORKERS ABOUT THE ACADEMIC EDUCATION OF NURSES IN BOSNIA AND HERZEGOVINA - Kucurski, Ljubisa; Pavlovic, Jelena; Savic, Ljiljana; Savic, Marko; Hadzivukovic, Natalija (HEALTH CARE, 2022)
Introduction/Aim: The problems facing the health sector in the Balkans, but also in most European Union countries (especially highly developed countries) is the lack of university-educated nurses in the labor market. The aim of the paper was to examine the attitudes of health professionals about the importance and possibilities of academic education of nurses.Methods: The cross-sectional study was conducted on 233 health workers in the period from July 10, 2019 to August 31, 2019 in the Public Health Institution (PHI) Health Center Zvornik, PHI Health Center Foca, PHI General Hospital Zvornik, PHI University Hospital Foca. All respondents filled out a questionnaire, which was previously culturally adapted. Χ2 was used in the statistical analysis of the data.Results: The majority of health workers (73.8%) were women. There were slightly more women under the age of 50, and men over the age of 50. There were 41.3% of doctors/specialists, 42.2% of nurses with secondary education, and 16.4% of nurses with post-secondary and higher education. The largest percentage of health workers (91.4%) state that they are familiar with the possibilities of nursing education, while 69.5% are of the opinion that thorough secondary education and specialization is enough for nurses. About half of health workers (50.2%), regardless of the level of education, states that there is no need for the education of nurses at the level of doctoral studies, and ¼ abstained on this issue. Doctors of medicine and specialist doctors and nurses with secondary education were statistically significantly more likely (χ2 = 10,151; p = 0.038) to consider that there is no need for education of nurses at the level of doctoral studies than nurses with post-secondary and higher education. The largest percentage of health workers (66.6%) have the opinion that the nurse has the same authority as other team members, 86.3% agree with the statement that the development of the nursing profession will affect the quality of health care, and 55.8% believe that nurses have the professional capacity, knowledge and experience to innovate solutions and manage the inevitable changes on the pathway to modern nursing.Conclusion: In order to raise the reputation of the nursing profession, it is necessary to define the scope of work and set clear boundaries between the competencies of nurses of different levels of education at the level of the whole of Bosnia and Herzegovina. In order to further develop the nursing profession, better promotion of new postgraduate programs is necessary.
Keywords: nursing, education, autonomy, competencies